Diverse modes of evolutionary emergence and flux of conserved microRNA clusters - Mohammed, Jaaved (RNA, 2014)
Many animal miRNA loci reside in genomic clusters that generate multicistronic primary-miRNA transcripts. While clusters that contain copies of the same miRNA hairpin are clearly products of local duplications, the evolutionary provenance of clusters with disparate members is less clear. Recently, it was proposed that essentially all such clusters in Drosophila derived from de novo formation of miRNA-like hairpins within existing miRNA transcripts, and that the maintenance of multiple miRNAs in such clusters was due to evolutionary hitchhiking on a major cluster member. However, this model seems at odds with the fact that many such miRNA clusters are composed of well-conserved miRNAs. In an effort to trace the birth and expansion of miRNA clusters that are presently well-conserved across Drosophilids, we analyzed a broad swath of metazoan species, with particular emphasis on arthropod evolution. Beyond duplication and de novo birth, we highlight a diversity of modes that contribute to miRNA evolution, including neofunctionalization of miRNA copies, fissioning of locally duplicated miRNA clusters, miRNA deletion, and miRNA cluster expansion via the acquisition and/or neofunctionalization of miRNA copies from elsewhere in the genome. In particular, we suggest that miRNA clustering by acquisition represents an expedient strategy to bring cohorts of target genes under coordinate control by miRNAs that had already been individually selected for regulatory impact on the transcriptome.